Avaliação da biocompatibilidade e bioatividade de membranas colágeno polianiônico mineralizadas e reticuladas em modelos animais - Veríssimo, Denusa Moreira (2012)
The aim of this study was to evaluate polyanionic collagen (PAC) membranes reticulated and impregnated with hydroxyapatite, manufactured by the Physics Department, Federal University of Ceará. This study was divided into two stages, initially it was evaluated the biocompatibility and biodegradation of six different membranes of PAC, divided into the following groups: three with 0, 25 and 75 cycles of impregnation with apatite (PAC, PAC 25, PAC 75 ) and three more whose membranes were crosslinked with glutaraldehyde (GA) (GA PAC, PAC 25GA, PAC 75GA) inserted into the subcutaneous tissue of rats. Histopathological analyzes of inflammatory infiltration, myeloperoxidase activity (MPO), cytokine, thickness of fibrous capsule, immunohistochemistry for metalloproteinase and degradation of the membranes were evaluated after 1, 7, 15, 30, 60 and 120 days. Subsequently, it was evaluated the effect of the three best membranes in guided bone regeneration using bone critical defects in rat calvaria (DOC), where the membranes were placed over the defect. Bone formation was evaluated based on digital radiography (DR), computed tomography (CT) and histological analysis, 24 hours, 4, 8 and 12 weeks after surgery. MPO and cytokine were performed after 24 hours. In the subcutaneous tissue, the membranes crosslinked with GA showed thick fibrous capsule, less inflammatory reaction and remained intact after 120 days. In the bone regeneration model in rat calvaria, after 12 weeks, PAC GA and PAC 25GA groups showed significant reduction in radiolucent area compared to the baseline group. Histological analysis showed that in PAC GA and PAC 25GA groups, membranes were still intact, surrounded by a thick fibrous capsule and in PAC 75GA group, membranes showed early resorption. There was no statistical difference between groups in MPO activity and IL-1β. We conclude that the crosslinked membranes were more biocompatible and remained free from degradation during the observation period. These membranes induced closure of bone defects and did not induce inflammatory reaction. The impregnation of hydroxyapatite did not accelerate the healing of surgical defect. Our results suggest that the crosslinked membranes CPA may be useful in cases where new bone formation is dependent on a longer duration of mechanical barrier.